Microtus pennsylvanicus ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
149. Meadow Vole Microtus pennsylvanicus French: Campagnol des prés / German: Wiesenwhimaus / Spanish: Topillo de campina Other common names: Admiralty Island Meadow Vole (admiraltiae), Block Island Meadow Vole (provectus), Chihuahua Vole (chihuahuensis), Penobscot Meadow Vole (shattucki), Potholes Meadow Vole (kincaid) Taxonomy. Mus pennsylvanica [sic] Ord, 1815, “meadows below Philadelphia,” Pennsylvania, USA. Twenty-seven subspecies recognized. Subspecies and Distribution. M.p.pennsylvanicusOrd,1815—extremeSEQuebecandNewBrunswick,Canada,andfromSouthDakota,N&ENebraska,andextremeNEKansasEtotheAtlanticcoastfromMaineStoSouthCarolina,USA. M.p.acadicusBangs,1897—PrinceEdwardIandNovaScotia,Canada. M.p.admiraltiaeHeller,1909—AdmiraltyI,Alaska,USA. M.p.alcorniBaker,1951—fromSWAlaska,USA,EtoSYukon,Canada. M.p.aphorodemusPreble,1902—SENunavutandNEManitoba,Canada. M.p.axtecusJ.A.Allen,1893—restrictedrangeinNWNewMexico,USA. ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 342, DOI: 10.5281/zenodo.6707142 ...